Assessment and Management of Chronic Musculoskeletal Pain Syndrome in Children: A Review - Rahman, Shahana Akhter; Haque, Mujammel; Islam, Mohammed Mahbubul (Bangladesh Journal of Child Health, 2017)
Musculoskeletal pain is a frequent complaint of children, is the most common presenting problem of children referred to pediatric rheumatology clinics. Chronic musculoskeletal (MSK) pain in children is responsible for substantial personal impacts and societal costs, but it has not been intensively or systematically researched. The majority of musculoskeletal pain complaints in children are benign in nature and attributable to trauma, overuse, and normal variations in skeletal growth. There is a subset of children in whom chronic pain complaints develop that persist in the absence of physical and laboratory abnormalities including growing Pain, juvenile fibromyalgia, complex regional pain syndrome. During recent years studies of the epidemiology, etiology and rehabilitation of pain and pain-associated disability in children have revealed a large prevalence of clinically relevant pain, and have emphasized the need for early recognition and intervention. Bangladesh J Child Health 2016; VOL 40 (3) :166-173